1998
DOI: 10.1021/jp972351e
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Photooxidation of Trichloroethylene on TiO2 and ZnO:  Influence of Trichloroethylene Pressure, Oxygen Pressure, and the Photocatalyst Surface on the Product Distribution

Abstract: Transmission Fourier transform infrared spectroscopy has been used to identify gas-phase and surface-bound products and intermediates formed during the gas-phase photooxidation of trichloroethylene (TCE) on TiO2 and ZnO. Several factors are found to influence the gas-phase product distribution for this reaction. On clean TiO2 and ZnO surfaces and at high TCE and O2 pressures, gas-phase CO, CO2, COCl2, CCl2HCOCl, CHCl3, C2HCl5, and HCl are produced, whereas at low TCE and O2 pressures, TCE is converted to gas-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…The amount of DCAC adsorbed on Sample T was three times greater than the initial amount of TCE. It is reported that TiO 2 can adsorb DCAC to some extent [17][18][19]24,29]. The adsorption capacities of Samples M and C for DCAC are about four times greater than that of Sample T. Figure 3 shows the changes in the average degradation rate of TCE during the repeated runs using Samples T, M, and C. The degradation rate increased with the repeated run for all the samples.…”
Section: Photocatalytic Degradation Of Tcementioning
confidence: 97%
“…The amount of DCAC adsorbed on Sample T was three times greater than the initial amount of TCE. It is reported that TiO 2 can adsorb DCAC to some extent [17][18][19]24,29]. The adsorption capacities of Samples M and C for DCAC are about four times greater than that of Sample T. Figure 3 shows the changes in the average degradation rate of TCE during the repeated runs using Samples T, M, and C. The degradation rate increased with the repeated run for all the samples.…”
Section: Photocatalytic Degradation Of Tcementioning
confidence: 97%
“…Similar to phosgene, trichloroacetaldehyde is also oxidized in combined system; following pathways for photocatalytic destruction of trichloroacetaldehyde have been reported (Driessen et al 1998;Fan and Yates 1996).…”
Section: By-productsmentioning
confidence: 94%
“…They reported that the degradation of TCE proceeded by active species, such as the hydroxyl radical, chlorine radicals [3,5−7,10−17], and adsorbed oxygen species [8,9].…”
Section: Introductionmentioning
confidence: 99%